Lifetime migrants and natives in the rural dry zone and urban Colombo - Abeysekera, D. (NARESA:Colombo, 1983)
This paper compares the two dominant streams of lifetime migrants in the rural dry zone and urban Colombo along with their native counterparts using the 1971 sample census data of Sri Lanka.Comparison of the two migrant streams reveal that Colombo attracted more males while the dry zone received relatively more females although both streams displayed a predominance of masculinity,more so in Colombo.Dependincy was higher in the dry zone as was the level of selectivity of single males.Female migrants are more married than males in both streams.Sri Lanka Tamils are the only ethnic group selected positively to both destinations while the Kandyan Sinhalese are over-represented in the dry zone;Buddhists are attracted more to the latter while the Christians are selected to Colombo.Migrants to Colombo,as might be expected,are better educated when controlled for age but the more interesting observation is that the females are better educated than males in the 15-19 age group at both destinations,a drastic reversal of what prevailed 30 years ago.Male migrants are more employed and less unemployed in the dry zone but a greater proportion of the older males have to keep-on working while a larger proportion of them in Colombo enjoy formalized social security benefits;females are relatively less employed and a higher proportion in the dry zone are engaged in home duties.When natives and migrants of each destination are contrasted children are greatly under-represented among the migrants resulting in lower dependency ratios in both Colombo and the dry zone.Among both the males and females the migrants are consistently better educated than the natives in each destination when age is held constant.Male migrants were less employed in Colombo than the natives while the reverse is true of the dry zone.Within each age group,greater proportions of female natives are engaged in home duties than migrants at both destinations.The native females marry earlier and exhibit higher fertility at both destinations.
Keywords: Migrant Categories; Fertility; Migrant Native Differentials; Migrant Status; Migration; Social Sciences